SOCIAL NETWORK COMMUNITIES’ SEARCH MODEL ABSTRACT - Akhramovych, Volodymyr; Lazarenko, Serhii; Martyniuk, Hanna; Balanyuk, Yuriy (Ukrainian Scientific Journal of Information Security, 2022)
. In order to ensure the smooth functioning of a social network with a large number of subscribers, it is advisable to divide it into subnets. Division into subnets will provide high-quality control of traffic and other parameters, including security parameters. The first reason for dividing the network into subnets is not to get a huge broadcast domain. The second important reason for dividing the network into subnets is to provide a certain level of security. The third reason is identifying online communities. The necessity of creating a model is determined. In this model graph is randomly generated with specified parameters for internal and external relationships between vertices, and communities are considered extraordinary. A method for isolating the structure of communities based on the maximum likelihood method is proposed, and a numerical random search algorithm is described on its basis. Graphs which representing real social and communication networks are changed rapidly. Moreover, random graphs are an effective tool for studying these networks. An important task is to identify the structure of communities in networks. In conditions of large dimensionality of networks, approximate methods are especially relevant. That allow finding a solution close to the optimal for a limited time. To solve this problem, it is proposed to create a model for distinguishing the structure of communities based on the maximum likelihood method. And a description of a numerical random search algorithm based on created model. This paper describes a mathematical model in which a graph is randomly generated with specified parameters for internal and external relationships between vertices, and communities are considered extraordinary. A method for isolating the structure of communities based on the maximum likelihood method is proposed, and a numerical random search algorithm using the Boltzmann-Gibbs distribution is described on its basis. The behavior of the objective function is investigated.